Leader Behaviors On Organizational Change in Multinational Company - Nurillah Jamil Achmawati Novel; Yudo Anggoro; Marsha Aulia Hakim (Universitas Padjadjaran, 2022)
Change is a certainty that occurs in a dynamic organization. The role of the leader in mobilizing and managing people in the organization greatly influences adaptation to change. This study aims to assess the behavior of leaders in multinational companies that are undergoing massive organizational change. Qualitative and quantitative approaches are used to optimally explore supporting data in analyzing leader behavior in organizational change. They involved respondents and participants from all divisions in the company. The results show that all dimensions tested are in the